Chemical Composition, in vitro Cytotoxic and Antioxidant Activities of the Fruit Essential Oil of Alpinia oxyphylla - Wang, Chengzhong; Yuan, Huihui; Bao, Xiaoli; Lan, Minbo (Asian Journal of Chemistry, 2014)
The aim of this study was to investigate in vitro cytotoxic and antioxidant activities of the fruit essential oil of Alpinia oxyphylla. The essential oil obtained by hydrodistillation was analyzed by GC and GC-MS. Seventy-four constituents were identified, of which valencene (19.04 g/100 g), calamenene (10.11 g/100 g) and nootkatone (8.97 g/100 g) were the main components. In vitro cytotoxicity of the oil on six human cancer cell lines was examined by Sulphorhodamine-B assay. The oil was very active against all tested cancer cell lines with the IC50 values ranging from 31.6 to 47.2 μg/mL. Antioxidant activity of the oil was determined by DPPH• and reducing power assay. The essential oil exhibited good reducing power in a dose-dependent manner and strong DPPH radical scavenging activity with IC50 value of 140.7 μg/mL. Our findings suggested that the essential oil could hold a good potential for use in food and pharmaceutical industry.